Educational Management of Indonesian Language Learning in UIN Fatmawati Sukarno Bengkulu - Flora Elefhentri; Heny Friantary; Vebby Andra (JMiE (Journal of Management in Education), 2026)
This study aims to analyze educational management in the Indonesian Language Education Study Program at Fatmawati Sukarno State Islamic University (UINFAS) Bengkulu, focusing on learning implementation and its supporting and inhibiting factors. The research employed a qualitative approach with a case study design. Data were collected through observations, in-depth interviews, and documentation involving lecturers, students, and program administrators selected through purposive sampling. Data validity was ensured through source and method triangulation. The findings revealed that educational management had been implemented effectively, as indicated by structured learning planning, the use of varied teaching methods, and systematic learning evaluation. Supporting factors included competent lecturers, a relevant curriculum, adequate learning facilities, high student motivation, and a conducive academic environment. Meanwhile, inhibiting factors consisted of students’ low basic language skills, limited facilities, uneven learning motivation, and less varied instructional strategies. The study concludes that the effectiveness of educational management is strongly influenced by the quality of human resources, infrastructure support, and adaptive learning strategies.